The neuroinflammatory hypothesis of delirium - Cerejeira, J (2010)
Delirium is a neuropsychiatric syndrome characterized by a sudden and global impairment in consciousness, attention and cognition. It is particularly frequent in elderly subjects with medical or surgical conditions and is associated with short- and long-term adverse outcomes. The pathophysiology of delirium remains poorly understood as it involves complex multi-factorial dynamic interactions between a diversity of risk factors. Several conditions associated with delirium are characterized by activation of the inflammatory cascade with acute release of inflammatory mediators into the bloodstream. There is compelling evidence that acute peripheral inflammatory stimulation induces activation of brain parenchymal cells, expression of proinflammatory cytokines and inflammatory mediators in the central nervous system. These neuroinflammatory changes induce neuronal and synaptic dysfunction and subsequent neurobehavioural and cognitive symptoms. Furthermore, ageing and neurodegenerative disorders exaggerate microglial responses following stimulation by systemic immune stimuli such as peripheral inflammation and/or infection. In this review we explore the neuroinflammatory hypothesis of delirium based on recent evidence derived from animal and human studies.